Decanoic Acid and Not Octanoic Acid Stimulates Fatty Acid Synthesis in U87MG Glioblastoma Cells: A Metabolomics Study - Damiano, Fabrizio; De Benedetto, Giuseppe E.; Longo, Serena; Giannotti, Laura; Fico, Daniela; Siculella, Luisa; Giudetti, Anna M. (Frontiers in Neuroscience, 2020)
Medium-chain fatty acids (MCFA) are dietary components with a chain length ranging from 6 to 12 carbon atoms. MCFA can cross the blood-brain barrier and in the brain can be oxidized through mitochondrial β-oxidation. As components of ketogenic diets, MCFA have demonstrated beneficial effects in different brain diseases, such as traumatic brain injury, Alzheimer’s disease, drug-resistant epilepsy, diabetes, and cancer. Despite the interest in MCFA effects, no much information is available about MCFA metabolism in the brain. In this study, by gas chromatography-mass spectrometry (GC-MS)-based metabolomics approach, coupled with multivariate data analyses, we followed the metabolic changes of U87MG glioblastoma cells after the addition for 24 h of octanoic (C8) or decanoic (C10) acids. Our analysis highlighted significant differences in the metabolism of U87MG cells after C8 or C10 addition and identified several metabolites whose amount changed between the two groups of treated cells. Overall, metabolic pathway analyses suggested citric acid cycle, Warburg effect, glutamine/glutamate metabolism, and ketone body metabolism as likely pathways influenced by C8 or C10 addition to U87MG cells. Our data demonstrated that, while C8 affected mitochondrial metabolism resulting in an increased ketone body production, C10 mainly influenced cytosolic pathways by stimulating fatty acid synthesis. Moreover, glutamine might be the main substrate to support fatty acids synthesis in C10-treated cells. In conclusion, we identified a metabolic signature associated with C8 or C10 addition to U87MG cells that can be used to decipher metabolic responses of glioblastoma cells to MCFA treatment.